Woody Plant Species with High Nutritional Value, Northeastern Mexico - Rodriguez, Humberto Gonzalez; Maiti, R. K.; Kumari, Ch Aruna; Sarkar, N. C. (International Journal of Bio-resource and Stress Management, 2017)
The study site was located at the Experimental Field of the Forest Science School, Universidad Autonomy de Nuevo Leon (24°47΄N; 99°32΄ W, 350 m asl), 8 km south of Linares county, Mexico. The present study has been undertaken to determine the variability in leaf nutrient contents (macroand micro) of 37 woody species in northeastern Mexico, which revealed the presence of large variability among the macro and micro-nutrient contents. By quintuplicate, mature leaf sample tissues were collected from each plant species and placed to dry on newspaper for a week. Leaves were removed from twigs and were passed through a mesh of 1.0×1.0 mm2 using a mill Thomas Wiley. Subsequently, they were dried for three days at 65 °C in an oven to remove moisture from the sample and later these were placed in desiccators. Among these 37 woody species of northeastern Mexico, the species containing highest P and Mg are Croton suaveolens (2.43 mg g-1 dry weight) and Ehretia anacua (9.45 mg g-1 dry weight), respectively, whereas Cordia boissieri recorded maximum K as 45.58 mg g-1 dry weight, Cu and Fe (30.71 and Fe 280.55 µg g-1 dry weight, respectively). Acacia schaffneri has 4.32% N (maximum) and Forestiera angustifolia 49.47% N. The species with highest C/N are Sargentia greggii 23.13 and Zn Salix lasiolepis (144.86 µg g-1 dry weight). The species selected for the highest macro- and micro-nutrients may be utilized for confirming their physiological efficiency and probable better growth and productivity.